Association between muscle relaxant dosage and recovery in pediatric otolaryngological surgery: A retrospective cohort study - Jingyu Tan; Youtan Liu (PLoS ONE, 2026)
Background Standardized guidelines for dosing strategies of muscle relaxants—specifically aimed at reducing extubation time and side effects—are currently lacking in pediatric otolaryngological surgery. This retrospective cohort study examined the association between induction dosages of neuromuscular blocking drugs and extubation times in children undergoing ambulatory procedures, aiming to provide evidence for future clinical decision-making. Objective This study examined the association between induction doses of muscle relaxants and two key outcomes in pediatric otolaryngological surgery: extubation times and the incidence of neuromuscular blockade-related complications (particularly residual paralysis and its clinical consequences, such as reintubation). The goal was to provide evidence that can inform dosing strategies aimed at accelerating recovery and minimizing adverse events. Methods A retrospective review was conducted using electronic medical records of pediatric patients who underwent otolaryngological surgery at Shenzhen Hospital, Southern Medical University;data access for research purposes occurred between June 23, 2020, and June 23, 2021. A total of 90 children, aged 3–12 and classified as ASA I-II, was included in this study. The patients were categorized into three groups based on the muscle relaxant used during surgery: R1 (0.4 mg/kg rocuronium bromide), R2 (0.6 mg/kg rocuronium bromide), and C (0.05 mg/kg cisatracurium). Extracted parameters included mean blood pressure (MBP), heart rate (HR), blood oxygen saturation (SpO₂), Cooper scores, Ramsay Sedation Scale (RSS), Agitation Scale (AS), extubation time, and surgery duration. Results The R2 group showed significantly higher mean blood pressure (MBP) than both R1 and C at T1 (both P < 0.05), and higher MBP than R1 and C at T2 (P < 0.01 and P < 0.05, respectively). Heart rate was significantly higher in both rocuronium groups compared to C at T1 and T2 (all P < 0.01). Cooper scores were significantly higher in R2 than in R1 or C (P < 0.01). No significant differences were found in SpO₂ at any time point (including T3 and T4), extubation time, surgery duration, RSS, or AS among groups (P > 0.05). No adverse events were observed in any of the three groups. Conclusion Despite the absence of pharmacological reversal, no clinical manifestations of residual neuromuscular blockade—including hypoxemia, reintubation, or severe emergence agitation—were observed in any group.Notably, rocuronium 0.6 mg/kg exhibited rapid onset, superior intubation conditions, and hemodynamic stability; extubation times and emergence quality were comparable among all groups receiving a single intubating dose of 1–1.5 × ED₉₅ of a neuromuscular blocking agent under the same intravenous-inhalation combined anesthesia.